Effect of micronutrients and plant growth regulators on fruit set and retention in ber (Ziziphus mauritiana Lamk.) (Indian Journal of Arid Horticulture, 2025)
The determination of fruit set has been used in ber as a consistent indicator of the real productivity level. Due to short flower life, prevalence of self and cross incompatibility, pollen sterility and synchronous protandrous dichogamy, fruit set in the ber largely depends on sources of pollination, its related factors like effective pollination period, pollinators, environmental conditions, and the success in fertilization. Hence, any factor that can extend the effective pollination period, pollen germination and pollen tube growth such as the application of micronutrient or plant growth regulators, should be beneficial for fruit production. During 2020– 21, forty-one genotypes of ber were evaluated for fruit set at ICAR-CIAH, Bikaner. Simultaneously, a trial was conducted to find out the response of micronutrients and plant growth regulators on fruit set and fruit retention in the ‘Gola’ ber. Foliar sprays of micronutrients (Boron at 0.1% and Zinc at 0.5%) and graded doses (10, 20, and 30 ppm) of plant growth regulators (GA₃, NAA, kinetin, and benzyladenine) were applied at BBCH stage 54 (green bud) and 67 (flower fading i.e. most petal fall). The genotypes showed large variation in natural fruit sets ranging from 0.34 (Chochal) to 13.89% (Illaichi). About 88 per cent of genotypes under observation exhibited fruit set less than 6 per cent. Intervention with micronutrients and plant growth regulators applied at two different stages bring a significant response on fruit set in Gola ber. Among the various treatments evaluated, the highest fruit set was observed with the application of 0.1% boron (B) at BBCH stage 67 (11.41%), followed closely by the application of 10 ppm gibberellic acid (GA3) at the same stage (10.94%). Both treatments were statistically on par in terms of fruit set. However, the boron treatment demonstrated a superior fruit retention rate (80.38%) compared to GA3 (63.68%). In contrast, the water-sprayed control trees recorded significantly lower fruit set (3.77%) and retention (56.52%). In conclusion, the application of Boron (0.1%) at BBCH stage 67 is an effective approach to enhance fruit set and retention in ber cv. Gola under the hot arid regions of Rajasthan.